Depression and associated factors among prisoners in Bahir Dar Prison, Ethiopia - Alemayehu, Fikirte (BMC Psychiatry, 2019)
BACKGROUND: Globally there is a rapid increase in prison population, and one out of nine inmates suffers from mental disorders like depression. In Ethiopia, although a mental health strategy is in place, little attention is given to prisoners and studies which focus on depression among prisoners are still scarce. The aim of this study was to assess the prevalence of depression and factors associated with it among prisoners. METHOD: Across-sectional study was conducted from October 5 to 28, 2016 in Bahir Dar city. Simple random sampling technique was used to select 402 prisoners. Depression was measured using Patient Health Questionnaire, nine item version (PHQ-9) at a cut point of five. Data on socio-demographic characteristics, behavioral factors, perceived general health, and prison situation variables were collected using structured questionnaire. The data were collected by trained interviewers. SPSS version 20 was used to analyze the data. Binary logistic regression was used to identify predictors of depression. RESULT: The prevalence of depression was 45.5% (95%CI: 40.5–50.5%). In the final model, having children [Adjusted Odds Ratio (AOR) = 2.48; 95%CI: 1.60–3.83], health satisfaction rated as moderate [AOR = 3.20; 95%CI: 1.12–9.00] or dissatisfied [AOR = 1.63; 95%CI: 1.02–2.62] compared to satisfied, being sentenced for more than 5 years [AOR = 2.31; 95%CI: 1.01–5.25] or 1–5 years [AOR = 3.04; 95%CI: 1.2–7.71] were positively associated with depression. CONCLUSION: High prevalence of depression was found among prisoners. Those with poor general health, long years of imprisonment, and concerns of children were the most vulnerable. Strengthening mental health services of prisons is critically required.